Solução de ringer lactato ou de cloreto de sódio a 0,9% em felinos com obstrução uretral aguda induzida experimentalmente - Cunha, Marina Gabriela Monteiro Carvalho Mori da (2008)
Felines with urethral obstruction are involved in a life-threatening situation, due to metabolic acidosis, hyperkalemia and hypocalcemia leading to hemodynamic abnormalities. The aim of this study was to compare the renal and cardiorespiratory stabilization in cats with experimentally induced urethral obstruction, submitted to a fluid therapy with Lactated Ringer s solution or 0,9% sodium chloride solution, during 48 hours after relief of urethral obstruction. Ten adult cats with induced urethral obstruction were used and randomly separated in two groups, which received Lactated Ringer s solution (RL group) or 0,9% sodium chloride (CS group) as fluid therapy. All the cats of the experiment had anorexia, metabolic acidosis, hyperkalemia and postrenal azotemia. At the moment of relief of obstruction, the cats were anesthetized by intravenous infusion of propofol (5 mg kg- 1). The infusion rates were gradually decreased. The initial rate was 20mL kg-1 h-1 until 6h and after it was decreased to 15mL kg-1 h-1 until 12 hours, 10mL kg-1 h-1 until 24 hours and 5mL kg h-1 until 48 hours of evaluation. The evaluations were done by analysis of pH, pCO2, pO2, HCO3 -, base deficit, anion gap, serum Na+, K+, Cl-, Ca2+, urea, creatinine, total protein, albumin, packed cell volume, total plasma protein, weight, heart rate, respiratory rate, rectal temperature, urinalysis and urinary output at different times for 48 hours. CS group presented metabolic acidosis at 0h and 2h and the RL group only at 0h. The CS group presented significantly lower values between the groups of parameters pH and HCO3 - between 8h and 48h and base deficit between 2h and 48h. Only the CS group presented hypernatremia at 12h and hypocalcemia at 2h. There were no statistically significant differences in the absolute blood potassium and chloride concentrations between groups at any time. After 24h of fluid therapy, 70% of the cats presented hypokalemia. Urinary output was significantly lower in the CS group at 8h. The infusion rates used were effective, because no fluid overload was observed in the animals of this experiment. Both crystalloid solutions used appear effective for fluid therapy in cats with induced urethral obstruction, however the Lactated Ringer s solution is more efficient on acid-base and electrolyte balance. The RL solution appears to be a safe option for felines with urethral obstruction.